A fully integrated three-axis thermal accelerometer - Silva, C. S. (2013)
A combined fabrication process using polymer and silicon planar microtechnologies is presented here and used for the fabrication of a fully-integrated three-axis thermal accelerometer. The use of polymers (polystyrene and polyimide) with low thermal conductivities improves the overall power consumption of the thermal accelerometer and enables a simple and low-cost fabrication process. The accelerometer is composed of 4 polystyrene microinjected structural microparts (two identical top parts and two identical central parts) and three polyimide membranes (two identical z-axis membranes and a central membrane). The microinjected parts provide the mechanical support for the active elements that are placed on the membranes (the heater and the temperature sensors). Fabricated microparts and membranes are presented and measurements performed on central membranes are used to characterize the heater. Experimental results reveal that a power of 58 mW is required to increase the temperature in the heater to 580K.